L’individualisation des politiques socioéducatives : famille sous assistance ou famille sous surveillance ? Le cas des « parcours individualisés de Réussite éducative » - Stéphanie Goirand (Recherches en Éducation)
From 2003 onwards, France is confronted with a rich but complex educational landscape. In addition to the Local Educational Contracts, devices such as the ‘Educational Success’ have appeared these last years. The characteristic of this device is to have a “preventive” function and to deal with young people and their families which are identified as ‘weakened’. The aim is to build individualised and transverse answers (at the educational, social or school level…) with respect to the identified issues. Through the study of the Educational Success Program, this article attempts to question the social effects induced by this individualization process of the “educational” public action towards families. If public policies are strongly interested in youth and family issues during these last decades, it is mainly a response to a social question. And if the requirement of the public administration for social risks is still so present, it is more and more in reference to a “combination of the social risks with the family risks”. This individualization of the reading scale of social problems has direct consequences on the elaboration of social and family policies. Here the goal is to understand in which way this reinforcement of public policies towards families and this form of “re-politicisation” of the private sphere contributes to modify the mechanisms of social regulation and to guarantee the maintain of ‘social cohesion’.